Socio-affectiveness and alternative figures of care for girls, boys and adolescents in Argentine legal praxis - Federico Pablo Notrica (Oñati Socio-Legal Series)
Both the legislation and the doctrinal and jurisprudential creation have begun to recognize the notion of socio-affectivity as a structuring element of family relationships among its members, often granting it primacy over the biological bond or relationships derived from kinship. Although affection has always been a constitutive component of human relations, the classical approach refused and refuses to recognize in it a source of Law and, as such, share the halo of legitimacy that kinship ties have enjoyed since ancient times. This resistance was able to generate many problems in reality, since the lack of legal recognition in some of the figures ruins the advances in the field of human rights. A clear example in Argentine legislation turns out to be the contents of articles 611, 643 and 657 of the Civil and Commercial Code on the prohibition of de facto guardians except the kinship bond between parents and guardians; or the delegation of the exercise of parental responsibility and the granting of custody of a child or adolescent, limiting it only to a relative. Well, while this legal limit occurs, reality prevails and, in some cases, the affective bond overlaps the biological one, owing value to the guiding principle of the best interest of the child to solve the problem raised. From this, the present work will try to demonstrate, through the analysis of the jurisprudence, the solutions reached that combine said guiding principle with the notion of socio-affectivity.